PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF KINETIKA REAKSI KOMPLEKS SEBAGAI UPAYA MENSTIMULASI KEMAMPUAN BERPIKIR SISTEMATIS MAHASISWA - Rina Elvia; Candra, I Nyoman; Nurhamidah (University of Bengkulu, 2025)
This study aims to develop interactive learning media on the topic of complex reaction kinetics as an effort to stimulate students' systematic thinking skills. This type of research is development research using the ADDIE model. The test subjects in this study were students of the Chemistry Education Study Program who participated in the Chemistry Kinetics course in the 2022/2023 academic year. The data collection techniques in this study included feasibility data from the developed media based on expert validation of the media and material, as well as responses from students participating in the course regarding the developed media. The instruments used in this study were a questionnaire on the needs of course participants, a validation sheet, and a student response questionnaire. The results showed that the interactive learning media developed was deemed very feasible from the perspective of media and material validation, with average percentages for media and material validation of 92.5% and 93.75%, respectively. The results of the response test of students taking the Chemical Kinetics course to the interactive media developed showed an average score percentage of 86.6% and was in the very good category. The responses of the students also showed that the media developed could stimulate students' systematic thinking skills in the topic of complex reaction kinetics.